2015
DOI: 10.5897/ajar12.164
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant activity of Malus domestica fruit extract from Kashan area

Abstract: Objective: Antioxidants are considered as the main factors in the inhibition of unwanted oxidation reactions. Materials and Methods: In this research the antioxidant potential of the fresh fruits of 4 cultivars (A to D) of Malus domestica (M. domestica) cultivated in the Kashan, Qamsar area was evaluated. The antioxidant activity of the samples were evaluated using two complementary antioxidant assays: 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and β-carotene/linoleic acid tests and the results were compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Studies reported that the apple peels show good activity than pulps [ 89 ]. It has been reported that water, alcohol, and polyphenol extracts of M. domestica fruit were found to be most effective against gram +ve and gram –ve bacteria such as B. subtilis, S. aureus, S. epidermidis, K. pneumonia , E. coli, and P. aeuroginosa, respectively, which could be usefully applied to the food, pharmaceuticals, and cosmetics industries [ 90 , 91 ]. It has been found that quercetin compound is abundantly present in apple peel, acts as an antioxidant, and the apple’s potential antioxidant activity was approximately 83µmol vitamin-C equivalents, which means that the antioxidant activity of 100 g apples is equivalent to about 1500 mg of vitamin-C [ 4 , 92 ].…”
Section: Medicinal Usesmentioning
confidence: 99%
“…Studies reported that the apple peels show good activity than pulps [ 89 ]. It has been reported that water, alcohol, and polyphenol extracts of M. domestica fruit were found to be most effective against gram +ve and gram –ve bacteria such as B. subtilis, S. aureus, S. epidermidis, K. pneumonia , E. coli, and P. aeuroginosa, respectively, which could be usefully applied to the food, pharmaceuticals, and cosmetics industries [ 90 , 91 ]. It has been found that quercetin compound is abundantly present in apple peel, acts as an antioxidant, and the apple’s potential antioxidant activity was approximately 83µmol vitamin-C equivalents, which means that the antioxidant activity of 100 g apples is equivalent to about 1500 mg of vitamin-C [ 4 , 92 ].…”
Section: Medicinal Usesmentioning
confidence: 99%
“…The findings of research study also confirmed that the pomegranate peel extract samples had higher antioxidant activity/percent inhibition owing to their high polyphenol content as compared to apple peel extracts. Sara et al (2015) testified the % inhibition of apple peel and it was found to be 63.92%. Kushwaha et al (2015) in their study articulated the DPPH radical scavenging activity of pomegranate peels about 63.74%.…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%
“…The generation of free radicals is the basic etiology of most human diseases condition, and there is an increasing need to develop techniques for measuring free radicals and their responses in vivo. These free radicals are so reactive that they have a short lifespan because of that, are not suitable for direct assays, and are determined by indirect methods where various end products of the target molecule like lipids, proteins, and DNA are measured quantitatively (Sara et al, 2015). The end product formed from the reactions of free radicals and biomolecules is more stable than free radicals.…”
Section: Resultsmentioning
confidence: 99%